Computational intelligence for privacy and security - Elizondo, David A.; Marti´nez-Balleste´, Antoni; Solanas, Agusti (Studies in computational intelligence, 2012)
This book collects papers on computational intelligence for privacy and security. The majority are extended versions of works presented at the special session on Computational Intelligence for Privacy and Security of IJCNN-2010